MODEL PENGAUDITAN BERBANTUAN KOMPUTER TERHADAP LAPORAN KEUANGAN PERGURUAN TINGGI NEGERI VOKASI BADAN LAYANAN UMUM - Zainal Abdul Haris; Sumiadji; Retno Widiastuti (Politeknik Negeri Malang, 2022)
The availability of databases resulting from the use of financial planning, management and reporting applications from vocational public tertiary institutions (polytechnics) of public service agencies is a resource that can be utilized for the purpose of achieving the effectiveness of auditing the resulting financial reports. However, the existence of these resources has never been exploited. Referring to these conditions, research was carried out which aims to develop a computer-assisted audit model of the financial reports of vocational colleges (polytechnics) of public service bodies through the use of database files generated by applications used in the financial administration of work units such as SAS, SIMAK BMN, and Inventory Application. The research method used is applied research. The object of research is the work unit of a vocational tertiary institution that applies the Public Service Agency Management Pattern. The results of the research are in the form of a computer-assisted auditing narrative model that describes the steps that must be carried out in computer-assisted auditing of the financial statements of vocational colleges that apply the Public Service Agency Financial Management Pattern.